The economics of microgrids - Khodaei, Amin; Arabnya, Ali (Wiley, 2024)
The global economy is transitioning into a future with resilient, low-carbon energy systems to adapt to and mitigate climate change's hazardous effects. Microgrids are localized grids that can connect to or disconnect from the power grid to operate autonomously, synchronously, or in isolation from it, as needed. Microgrids are capable of operating while the main grid is down, so they can strengthen grid resilience by mitigating grid disturbances and facilitating a faster system response and recovery. In addition, they can enable large-scale adoption of distributed renewable energy resources such as solar and wind."--